PERAN PEREMPUAN SINGLE PARENT DALAM PEMENUHAN FUNGSI EKONOMI DALAM KELUARGA Studi Kasus: Perempuan Single Parent Pekerja di Pijat Refleksi Tosyma Jakarta Selatan - Havizathul Hanim (Universitas Nasional, 2018)
This paper aims to explain the role of single parent women, especially in the Tosyma Reflection Massage in South Jakarta. Becoming a single parent, especially for a woman, has its own difficulties where she has to fulfill functions within the family, especially the economic function which is the key to strength in the family to fulfill life's needs. Single parent women will look for any job so that their daily needs are fulfilled. The results show that women who become the head of the household and the main breadwinner experience problems such as the non-fulfillment of economic needs. Reduced interaction and disruption of communication with children and psychological problems that have a negative impact on the fulfillment of family functions.